Optimization of Customer Satisfaction for Green Design and Decision-Making Method - Lara F. Hourani (Modern Perspectives in Economics, Business and Management Vol. 7, 2021)
The objective presents Kano model to measure customer satisfaction for the eco-efficiency and green design. This method can be used to support the designer for reducing the environmental impact of the product throughout its life cycle and as a supporting tool for designers to invent novel, useful, and environmentally friendly products, our approach is to develop this method by linking concepts from marketing and environments to show the competitive advantage of creating a high level of customer satisfaction by adopting the requirements of the eco-efficiency and green design. For that I will begin with a brief discussion for the eco-efficiency and green design then identify the requirements of the eco-efficiency and green design and lastly propose Kano model to measure customer satisfaction for the eco-efficiency and green design. Kano’s model of customer satisfaction, a methodology is introduced which determines which influence the components of products and services have on customer satisfaction. And also demonstrate how the results of a customer survey can be interpreted and how conclusions can be drawn and used to demonstrate customer satisfaction for eco-efficiency and green design. As we see the result of the study shows that the eco-efficiency and green design for the goods and services have a competitive advantage.